2021
DOI: 10.3390/jcm10153232
|View full text |Cite
|
Sign up to set email alerts
|

Changes over Time in Hemoglobin A1C (HbA1C) Levels Predict Long-Term Survival Following Acute Myocardial Infarction among Patients with Diabetes Mellitus

Abstract: Frequent fluctuations of hemoglobin A1c (HbA1C) values predict patient outcomes. However, data regarding prognoses depending on the long-term changes in HbA1C among patients after acute myocardial infarction (AMI) are scarce. We evaluated the prognostic significance of HbA1C levels and changes among diabetic patients (n = 4066) after non-fatal AMI. All the results of HbA1C tests up to the 10-year follow-up were obtained. The changes (∆) of HbA1C were calculated in each patient. The time intervals of ∆HbA1C val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…High levels of glycated haemoglobin lead to a reduction in the body's ability to compensate for hypoxia, which has an effect on the establishment of collateral circulation and consequently on the recovery of cardiac function. High levels of glycated haemoglobin trigger abnormalities in the body's endothelial function, making the atherosclerotic plaque less stable and increasing the incidence of untoward events [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of glycated haemoglobin lead to a reduction in the body's ability to compensate for hypoxia, which has an effect on the establishment of collateral circulation and consequently on the recovery of cardiac function. High levels of glycated haemoglobin trigger abnormalities in the body's endothelial function, making the atherosclerotic plaque less stable and increasing the incidence of untoward events [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on specic epidemiologic studies, individuals who have diabetes have a four times higher chance of mortality from cardiovascular disease (CVD). 5 Studies have revealed a substantial gender disparity in the incidence and prognosis of acute myocardial infarction (MI) and coronary artery disease (CAD). Women are inclined to have potential risks such as systemic hypertension and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…7 Cardiovascular diseases (CVD) are mostly involved in mortality of type 2 diabetic patients accounting for about 75%. 8 According to some epidemiological studies, diabetic patients have four folds increased risk of CVD mortality. 9 Studies have shown a significant gender based difference in the prevalence and prognosis of coronary artery disease and acute myocardial infarction (AMI).…”
Section: Introductionmentioning
confidence: 99%